Sacred Power in Secular Politics: Exploring the Role of Orthodox Christian Organizations in U.S. Foreign Policy - Wu, Landuoer (Eximia, 2024)
This paper aims to examine the involvement and influence of religious non-state actors (RNAs) in the decision-making processes of United States foreign policy. It aims to provide insights into the reasons, mechanisms, and circumstances that lead such entities to engage in foreign policy and influence state actions. Principally utilizing primary sources, it presents original data with a unique glimpse into the strategies employed by RNAs. The paper shows that RNAs can informally but significantly participate in foreign policy decision-making by spotlighting a less-researched area that exists alongside formal initiatives.